Transformation of social values during a pandemic and problems of global solidarity - Vira Dodonova; Roman Dodonov (Cхід, 2020)
The paper analyzes the current situation in the world during the coronavirus pandemic, in particular, the general trend to border closure, isolation, national selfishness, increase in total control, and “secucracy”. The paper puts forward a question of reinterpretation of the significance of material values; actualization of post-material values: friendship, love, respect for the Other, self-actualization, family, and environmental values. Based on P. Sorokin’s model of universal altruism, the value shift amidst the pandemic has been analyzed. It is proved that during the severe periods of human development the values of natural law, namely the right to life, the right to health, the right to freedom assume great importance.